Data from: Linking habitat composition, local population densities and traffic characteristics to spatial patterns of ungulate-train collisions ... - Jasińska, Karolina D.; Żmihorski, Michał; Krauze-Gryz, Dagny; Kotowska, Dorota; Werka, Joanna; Piotrowska, Diana; Pärt, Tomas (Dryad, 2019)
1. Total length of railways worldwide exceeds 1 million kilometres and recent railway development directly impacts wildlife because of animal-train collisions. Few studies, however, have analysed factors driving ungulate-train collisions. 2. We analysed over 3500 ungulate-train collisions including roe deer, red deer, wild boar, and moose collected in 2012-2015 in Poland. We compared train traffic characteristics (e.g. traffic intensity, speed, rail curvature), land-use and habitat characteristics (e.g. share of forests and build-up areas) and local ungulate population densities at collision sites and random sites distributed along the rail network. 3. Forest coverage generally increased, while urban areas decreased ungulate collision risk. Local density of ungulate species was strongly positively related to the relative collision risk in all four ungulate species, but above certain densities, the risk levelled off for all four species. 4. Train speed and train traffic intensity were positively associated ... : Ungulate-train collision databaseA database with over 3500 ungulate-train collisions and over 10 000 random localities along Polish railways, used in analyses published in Jasińska et al. Journal of Applied Ecology (2019). The databse is incomplete, however, as we do not own data provided by Polish Railways PKP.railways_database.xlsxrailways_database_Readme.txt ...